Etika Kerja Islam dan Realitas Upah Pengrajin Tapis Lampung: Kajian Ekonomi dan Tradisi Lokal - Wahid, Moh. Abdur Rohman (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study aims to analyze the work ethic of tapis craftsmen in Lampung and examine the economic realities of their wages within the framework of Islamic values. The research seeks to understand the relationship between work ethic and the economic conditions of tapis craftsmen, as well as their resilience in preserving tradition despite financial constraints. A qualitative approach was employed, incorporating interviews and observations with business actors and tapis craftsmen in Metro City and East Lampung. Data were collected through direct engagement with craftsmen to explore their work ethic and financial challenges. The findings indicate that tapis craftsmen exhibit a strong work ethic, characterized by diligence, responsibility, and commitment. However, they face significant economic difficulties due to wages that remain below the standard living wage. This disparity poses a challenge to both their livelihood and the sustainability of tapis craftsmanship as a cultural heritage. Theoretically, this study underscores the necessity of aligning economic justice with Islamic ethical values in labor practices. The findings emphasize the need for fairer wage policies and empowerment programs to support tapis craftsmen, ensuring both economic well-being and the continuity of local traditions.